A study of the performance of the PNP-Iloilo City Proper policemen of the City Ordinance No.84 - Cabrera, Analiza G.; Guartero, Gervill O. (1995.)
The study evaluated the performance of the PNP-Iloilo City Proper policemen on the implementation of the City Ordinance No. 84 by determining whether they are doing their duty strictly according to the provision of the said ordinance and the factors which influences them. This is to answer the question at present if they do their duty of arresting the violators of this ordinance. The Iloilo City proper is the location of the study, since it is one of the concerned areas of the said ordinance - has a primary purpose of safeguarding the health of the concerned citizens. An interview guide was used to gather the data needed so that the researchers could get more information than using a questionnaire. As a generaal observation, it is said that these law enforcers are not performing their duty resulting to the noticeable existence of violators. several factors were identified which has affected the performance of the enforcers. Enforcers also expressed their side to justify their actions. With these, the researchers had made conclusions and recommendations that would encourage all affected parties of this ordinance.
Research Paper (BA 200). -- [Iloilo City] : University of the Philippines in the Visayas - College of Management], April 13, 1995.